(untitled) (المجلة العراقية للعلوم الاقتصادية, 2023)
This study delves into the underlying dynamics and causes of Iraq’s real estate price bubble, focusing on key parameters such as real estate factors, government policies, economic indicators, and societal trends. Drawing on comprehensive data from the past decade, the analysis was carried out using a sample of 65 real estate professionals and stakeholders in Iraq’s major urban centers. Sophisticated statistical tools, including SPSS V.25 and Smart PLS, were employed to analyze the data, pinpointing factors like real estate demand-supply dynamics, lending practices, and economic policies. The study unveiled that a combination of rapid urbanization, speculative investments, lax lending practices, and certain government policies contributed to the inflation of property prices, leading to the current bubble. Additionally, the study underscores the potential repercussions of this bubble on Iraq’s broader economy and housing affordability for its citizens. Recommendations are proposed, emphasizing the need for more stringent lending criteria, transparent property valuation practices, and government interventions to stabilize the market and prevent a potential crash.